Clinical and Postoperative Outcomes of Cancer Surgeries during the COVID-19 Pandemic: A Comparative Study with its Pre-COVID Surgical Audit at Five Major Tertiary Care Hospitals’ Cancer Departments in India - Heroor, Anil; Talwar, Rajnish; Joshi, Rama; Nayak, Sandeep; Naik, B. Niranjan; Tiwari, Alok; Jain, Sushil Kumar; Kapoor, Rajeev; Jagad, Vijay; Bansal, Naval; Gangadhara, Bharath; Bora, Rashmi; Verma, Harish; Nambiar, Yadhukrishnan; Patil, Akshay; Singhavi, Hitesh (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction There has been an exponential rise in number of coronavirus disease 2019 (COVID-19)-positive infections since March 23, 2020. However, cancer management cannot take a backseat.Objective The aim of this study was to identify any difference in the complication and mortality rates for the cancer patients operated during the ongoing COVID-19 pandemic.Materials and Methods This was a retrospective study of a prospectively maintained database of five centers situated in different parts of India. Variables such as demographics, intraoperative, and postoperative complications were compared between COVID-19 (group A—March 23, 2020–May 22, 2020) and pre-COVID time period (group B—January 1 to January 31, 2020).Results One-hundred sixty-eight cancer surgeries were performed in group B as compared with 148 patients who underwent oncosurgeries in group A. Sixty-two percent lesser cancer surgeries were performed in the COVID-19 period as compared with the specific pre-COVID-19 period. There was no significant difference in age group, gender, comorbidities, and type of cancer surgeries. Except for the duration of surgery, all other intraoperative parameters like blood loss and intraoperative parameters were similar in both the groups. Minimally invasive procedures were significantly lesser in group A. Postoperative parameters including period of intensive care unit stay, rate of infection, need for the change of antibiotics, and culture growth were similar for both the groups. While minor complication like Clavien-Dindo classification type 2 was significantly higher for group A, all other complication rates were similar in the groups. Also, postoperatively no COVID-19-related symptoms were encountered in the study group. A subset analysis was done among the study groups between those tested preoperatively for COVID-19 versus those untested showed no difference in intraoperative and postoperative parameters. No health-care worker was infected from the patient during the time period of this study.Conclusion Our study shows that there is no significant difference in the incidence of postoperative morbidity and mortality rates in surgeries performed during COVID-19 pandemic as compared with non-COVID-19 time period.
Keywords: pandemic; COVID-19; cancer surgery; outcomes; complication rates